2010
DOI: 10.1007/s11069-010-9513-x
|View full text |Cite
|
Sign up to set email alerts
|

Driving factors for social vulnerability to coastal hazards in Southeast Asia: results from the meta-analysis

Abstract: Several decades of research has produced considerable understanding of the complex and interacting factors contributing to the construction of social vulnerability to natural hazards. However, natural hazards remain a considerable challenge to poverty reduction and development in many countries around the world and particularly in South and Southeast Asia. The objective of this paper is to undertake a comprehensive systematic analysis of the scientific literature on coastal hazards to identify the factors cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Those conditions build upon wider, historically embedded socio-political and economic processes (Wisner and Cannon, 2005). Within their meta-analysis, Zou and Wei (2010) identified driving factors for social vulnerability to coastal hazards in Southeast Asia, including population growth, migration to the coast, poorly planned urbanisation and tourism development, which lead to land-use changes and transformations of ecosystems. Those processes in turn also constitute the vulnerability of a system.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Those conditions build upon wider, historically embedded socio-political and economic processes (Wisner and Cannon, 2005). Within their meta-analysis, Zou and Wei (2010) identified driving factors for social vulnerability to coastal hazards in Southeast Asia, including population growth, migration to the coast, poorly planned urbanisation and tourism development, which lead to land-use changes and transformations of ecosystems. Those processes in turn also constitute the vulnerability of a system.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For contemporary communities around the world, each situated in a distinct social-ecological context and each with their own histories and visions for the future, anthropogenic change is occurring with increasing rapidity, complexity and uncontrollability (IPCC 2014;Steffen et al 2015). The drivers of these changes occur at different scales and speeds and include environmental, climatic, economic, technological, sociocultural, demographic and governance factors (Millenium Ecosystem Assessment 2005;Zou and Wei 2010;Bennett et al 2014b). Communities are exposed to these exogenous changes through direct and indirect impacts on the interrelated components of social-ecological systems (Turner et al 2003;Perry et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in many cases the bottomup approaches taken in empirical studies have led to results that: (a) fail to explore the breadth of changes to which communities are exposed and (b) inadequately examine how these changes interact to produce variable outcomes for linked social and environmental assets that are important to local communities. Indeed, few case studies of coastal vulnerability are guided by conceptual frameworks, which have led to limited comparability among sites, countries and regions (Zou and Wei 2010). Typically, these conceptual and empirical approaches simplify the scope of changes to which communities are exposed, invariably leading to onedimensional adaptation policies, programs and actions that fail to address the multifaceted and multi-scalar drivers of change, and the complexity and uncertainty of changes in local social-ecological systems.…”
Section: Introductionmentioning
confidence: 99%
“…The 36 stressors that emerged from the interviews were categorized as socio-economic stressors (i.e., social, governance and conflict, economic) and biophysical (i.e., climate change and other environmental). The stressors identified in this case study are not unique to this locale (Zou & Wei, 2010). The rating of these stressors through a household survey demonstrated that certain stressors were perceived to have a higher impact -particularly economic stressors and some climatic and environmental stressors -than others.…”
Section: Discussionmentioning
confidence: 66%
“…The stressors facing coastal communities, and associated ecosystems, include social, economic, institutional, political, demographic, livelihood, and other environmental changes (Perry et al, 2010;Zou & Wei, 2010). Many authors have argued that it is important to understand the interactions between global environmental changes, including climate Vulnerability to Multiple Stressors 2 change, and other social, economic, and political changes occurring at multiple spatial and temporal scales in order to create effective adaptation policy (e.g., O'Brien & Leichenko, 2000;Silva et al, 2010;Turner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%